The Impact of Explosive Box Counseling on Improving Knowledge and Attitudes of Reproductive-Age Couples to Prevent Stunting - Rahmiwati, Anita; Aggraeni, Deliza (Sekolah Tinggi Ilmu Kesehatan Harapan Ibu Jambi, 2023)
Background: Stunting is a nutritional problem due to nutrient deficiency during the first 1000 days of life. Efforts to prevent the occurrence of stunting are essential, considering the impact that will be caused. One way is to provide health education to couples of childbearing age so that they can prepare for their pregnancies well. This study aimed to determine the effect of counseling using explosion boxes to increase the knowledge and attitudes of fertile-age couples. This research uses an analytical, operational study with a quasi-experimental research design with a non-equivalent control group design. This research was conducted by providing health education as a form of intervention that was preceded by measurement of knowledge before and after the intervention. Method: The study used a quasi-experimental method with a non-equivalent control group design. This research sample is a fertile age couple in the working area of the Office of the Religious Affairs of Sirah Pulau Padang,Ogan Komering Ilir Distric (OKI) which amounted to 64 respondents. The sampling method uses purposive sampling.The experiment group with the Explosion Box for media education and the control group with the lecture method which was previously given a pretest first and after 14 days. Furthermore, it was analyzed with a dependent sample t-test and an independent sample t-test. Results: The study showed that there was a significant influence in increasing knowledge both in the experimental group (p = 0,000) and the control group (p = 0,000) and the good attitude in the experimental group (p = 0.003) and the control group (p = 0,000). Furthermore, there was no significant difference between respondents' knowledge in the experimental & control group (p = 0.413) with a difference of 0.78 and the attitude of the experimental & control group (p = 0.607) with a difference of 0.98. Conclusion: Counseling with an explosion box is more effective in increasing the knowledge and attitudes of fertile-age couples, even though there is no statistical difference between an explosion box and a lecture. Keywords: Lecture, Explosion box, Knowledge, Attitude, Stunting